New type of CFRP reinforcement and technique for the flexural strengthening of RC balconies - Barros, Joaquim A. O. (2022)
The present work assesses the potentialities of a new carbon fibre reinforced polymer (CFRP) bar, applied according to a hybrid technique for the flexural strengthening of cantilever type reinforced concrete (RC) structures, such as the case of RC balconies. The CFRP bar is formed by an inclined extremity that is inserted into a hole according to the embedded through section (ETS) technique, a part that is applied according to the nearsurface mounted (NSM) technique, and a transition zone between these two parts. The anchorage conditions of the ETS part of the CFRP bar allow limiting the strengthening intervention to the cantilever zone of the balcony, with an almost null intrusion to the interior of the building. The effectiveness of this CFRP reinforcement and technique was assessed by testing 9 double-sided RC balcony prototypes, in a total of 18 tests. The inclination of the ETS part of the CFRP bar (15◦ and 30◦), the concrete strength class (C25 and C35) and the ratio of existing flexural tensile reinforcement (ρls=0.28% and 0.44%) were the variables investigated in terms of flexural strengthening performance. The results showed that the strengthening effectiveness has increased with the decrease of the inclination of the ETS part of the CFRP bar. A reinforcement ratio of 0.17% of CFRP bars with an extremity at 15◦ inclination, has doubled the load-carrying capacity of the corresponding reference prototypes. The applicability of the most recent formulation of the fib bulletin 90 for the flexural strengthening of RC elements with NSM CFRP reinforcements was assessed for this type of application. The ratio between maximum load registered experimentally and predicted with fib formulation was 0.95 with a standard deviation of 0.08. However, this high level of predictive performance requires the effective tensile strength of the transition zone of the CFRP bar to be known, which is still a critical aspect of the current generation of CFRP bars. A numerical approach was developed, capable of estimating the force–deflection, the strains and stresses in the constituent materials and evolution of stiffness degradation of the strengthened structures during the loading process, and its high predictive performance was also demonstrated by simulating the experimental tests carried out.